Mapping the Alternative Locations of Street Vendor Stabilization in Surakarta, Indonesia - Murtanti Jani Rahayu; Imam Buchori; Retno Widjajanti; Rufia Andisetyana Putri (Geoplanning: Journal of Geomatics and Planning, 2019)
The arrangement of street vendors is continuously undertaken by the government of Surakarta City for the sake of attaining the city order and public welfare. The inclination of the Stabilization success level in achieving the goal of street vendor arrangement strategy indicates that the location characteristics conforming to the street vendors’ preferences become one of the determinations in terms of the arrangement success. This article aims at mapping the alternative locations of street vendor Stabilization in Surakarta by applying the spatial analysis resting upon Geographic Information System (GIS) by means of two stages. They encompass: 1) identifying the conditions of the existing street vendor Stabilization locations, and 2) formulating the alternative locations of street vendor Stabilization based on the criteria which entail the proximate main activities, the crowds of environment, and the availability of state-owned land. The result of spatial analysis indicates that there are 19 alternative locations in Surakarta which are aligned with the criteria and can be utilized for new street vendor Stabilization locations.